The The reshaping of medical image by news reports during COVID-19 ’s epidemic situation - Lu, Xinyan; Lu, Yijing; Le, Siyu; Li, Yazheng (Advances in Social Sciences Research Journal, 2021)
Medical image has always been a long-term topic in social life, through questionnaires and personal interviews to investigate the role of news reports on the reconstruction of medical image before and after the epidemic. Through the investigation, it can be found that the media has played a certain intermediary role and positive guiding role in the alleviation of doctor-patient relationship and the shaping of medical portrayals; some metaphorical discourse descriptions in news reports can achieve better communication effect; through a variety of reporting forms and attribute agenda settings, the media enriches the foreground image of doctors and indirectly shapes the social image of doctors.